The Impact of Central Bank Policy on Aspects of Bank Sharia Financial Behavior in the Money Market - Nuzhuliya Mega Avifa; Samsul Arifin; Ida Farida (Al-Fadilah: Islamic Economics Journal, 2024)
Central bank policy has an important role in influencing the behavior of banks in the money market. This is important because banking movements can affect market stability and the economy as a whole. Therefore, analysis of the impact of central bank policy on bank behavior is very important to expand understanding of how monetary policy can influence the actions of banks participating in money markets. The research results show that central bank policies such as changes in interest rates, mandatory reserve policies, and market intervention have a significant impact on bank behavior. Interest rates set by the central bank can affect bank lending and investment interest, while mandatory reserve policies can affect banks' liquidity and their risk management strategies in the money market. This study also emphasizes the importance of transparency and communication from central banks in implementing policies. Clarity in policy can indirectly help in managing market expectations and help banks respond to changes in monetary policy. This research can be the basis for further research exploring how central bank policies can improve risk and liquidity management, as well as the stability of money markets and the economy. In conclusion, central bank policy has a significant impact on bank behavior in the money market, and policy communication and transparency are important factors in bank risk and liquidity management in order to maintain money market stability in the future.